Effects of naftidrofuryl on breathlessness and exercise tolerance in chronic bronchitis. Issue 8 (August 1982) - Williams, A J; Osman, J; Skinner, C
Abstract : Naftidrofuryl enhances oxidative phosphorylation and might therefore be expected to improve exercise tolerance and breathlessness in advanced chronic bronchitis. This hypothesis was tested in a four-week placebo-controlled trial in 11 bronchitic patients. Seven patients completed the study. There was no evidence of any benefit from naftidrofuryl either subjectively or after a 12-minute walking test.